The Analysis of Mathematics Academic Burden for Primary School Students Based on PISA Data Analysis - Wang, Li (Frontiers in Psychology, 2021)
It is aimed to explore the current situation of the mathematics academic burden of primary school students in China, as well as the relationship between the academic burden with the physical and mental health of students. Taking Program for International Student Assessment (PISA) as the starting point, the importance of cultivating students' mathematical literacy is discussed through the investigation of the recognition of students' mathematical literacy by PISA. Also, the correlation between the mathematics academic burden with the laws of mathematics teaching and students' physical and mental development is explored. Therefore, through the questionnaire survey, the root cause of the academic burden of students is investigated. In addition, the understanding of parents, teachers, and students about the mathematics academic burden is analyzed. Also, the discussion is carried out on this basis. The results show that students, teachers, and parents have a general understanding of the mathematics academic burden of primary school students at this stage. 67% of teachers believe that primary school students have a heavy burden on mathematics. 61% of parents believe that primary school students are under heavy academic stress. 60% of primary school students believe that the mathematics academic burden is heavy, which has led to a reduction in sleep time and extracurricular activities. It has a serious impact on the physical and mental health of primary school students. This investigation provides references for improving the balance between current education and the development of students' physical and mental health in China.